General anesthesia vs. sedation in transcatheter aortic valve implantation (TAVI): retrospective study of the incidence of acute kidney injury. - Fernando Jorge Rocha Simões (2020)
Objective(s): The aim of this study was to assess the existence of association between anesthetic approach (general anesthesia versus sedation) for patients undergoing transcatheter aortic valve implantation (TAVI) and the postoperative acute kidney injury (AKI) incidence. As secondary outcome we also assess the association between anesthesia type and mortality. Design: Retrospective, single-center, observational study. Setting: Centro Hospitalar Universitário de São João, a Portuguese reference center. Participants: All patients undergoing TAVI from January 2015 to June 2018. Interventions: General anesthesia (GA) or sedation for TAVI procedures. Measurements and Main Results: The primary outcome was AKI incidence, and secondary outcome included in-hospital, 30-day and 90-day mortality. In the period studied, 107 patients underwent TAVI (GA: n=24; sedation: n=83) and the overall incidence of AKI was 14.02%. We found a higher incidence of intraoperative hypotension in the GA group (83.3% vs 33.7%, p<0.001). Regarding postoperative outcomes, there were no significant differences in AKI incidence (20.8% vs 12.0%, p=0.319) and mortality. The major finding of interest was the significant association between postoperative AKI and preexisting chronic kidney disease (CKD), preoperative heart failure functional class, intraoperative hypotension, longer length of stay in level II unit and longer hospital stay, and worsening of previous CKD stage. Conclusions: It was not possible to established association between the anesthetic approach for TAVI procedures and postoperative AKI and mortality. Our study reinforces the importance of preventing AKI incidence, considering its impact on the worsening of baseline CKD and on the length of stay, leading to higher hospitalization costs.